A new synergetic mesoporous silica combined to CdSe-graphene nanocomposite for dye degradation and hydrogen evolution in visible light. (November 2018) - Nguyen, Dinh Cung Tien; Zhu, Lei; Zhang, Qinfang; Cho, Kwang Youn; Oh, Won-Chun
Graphical abstract: Highlights: The SiO2 /CdSe-graphene material is capable of photocatalytic degradation of different organic dyes under visible light irradiation. The large surface area of silica was provided a large response surface with a large quantity of reactions centers that needed H2 generation. High H2 generation can be attributed to the effective charge carrier system and a good charge transferability of graphene decorated with SiO2, and CdSe semiconductors. The ternary catalyst holds promise to become a new potential photocatalyst for developing efficient hetero-system for hydrogen production. Abstract: To promote outstanding qualities of mesoporous silica and enhance photocatalytic activity of CdSe and silica nanoparticles, the combination of SiO2 nanoparticles from silica precursor with CdSe-graphene nanoparticles was processed under catering of cetyltrimethylammonium bromide (CTAB) and sodium lauryl sulfate (SLS) as the surfactant template. The as-synthesized sample exhibited highly efficient photocatalytic effects for treatment of MB and RBB organic dye solutions at optimum conditions for this study, including pH and catalyst dosage, were at pH 11 for MB dye solution case and pH 3 for RBB dye solution case and initial amount was 0.05 g catalyst for both cases. Besides, hydrogen generation of SiO2 /CdSe-graphene was markedly higher than that of binary CdSe-graphene nanocomposite under ambient conditions with/without methanol 20% sacrificing reagents at room temperature. The SiO2 /CdSe-graphene nanocomposite is capable of photocatalytic degradation of different organic dyes under visible light irradiation as well as for developing efficient hetero-system for hydrogen production.